2020
DOI: 10.7554/elife.52189
|View full text |Cite
|
Sign up to set email alerts
|

Distinct inactive conformations of the dopamine D2 and D3 receptors correspond to different extents of inverse agonism

Abstract: By analyzing and simulating inactive conformations of the highly homologous dopamine D2 and D3 receptors (D2R and D3R), we find that eticlopride binds D2R in a pose very similar to that in the D3R/eticlopride structure but incompatible with the D2R/risperidone structure. In addition, risperidone occupies a sub-pocket near the Na+ binding site, whereas eticlopride does not. Based on these findings and our experimental results, we propose that the divergent receptor conformations stabilized by Na+-sensitive etic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 56 publications
2
46
0
Order By: Relevance
“…2,[21][22][23] Likewise, mutation of Trp100 ECL1 Ala increases the association and dissociation of antagonist ligand risperidone. 24 The hD3 simulations lead to a very similar result (Fig. S2b, ESI †).…”
supporting
confidence: 54%
“…2,[21][22][23] Likewise, mutation of Trp100 ECL1 Ala increases the association and dissociation of antagonist ligand risperidone. 24 The hD3 simulations lead to a very similar result (Fig. S2b, ESI †).…”
supporting
confidence: 54%
“…Indeed, ECL2 in 5-HT 2A R moves slightly to bind a different ligand 26 . An MD simulation study also suggested these dynamics of the ECL2 of D 2 R 47 and reported that the helical conformation of ECL2 observed in D 2 R ris tended to unwind toward an extended conformation, similar to that of D 3 R eti , regardless of the bound ligand, including spiperone, risperidone, or eticlopride 47 . The unwinding involves a drastic rearrangement of the side chain of Ile183 45.51 , dissociating from a hydrophobic pocket.…”
Section: Discussionmentioning
confidence: 87%
“…Thus no main difference was expected. In reality the results show differences in D2 inactive conformation that suggest different receptor inactive states ( Lane et al., 2020 ). In addition the agonist binding pocket in the D2 allows an extension that has been used to study D2 > D3 and D4 selectivity (with agonist ligands) and to determine the possibility to obtain biased agonists for D2 ( Fan et al., 2020 ).…”
Section: Section 3 Dr Ligands and Scz Therapies The New Wave Of Ligmentioning
confidence: 99%